Pengaruh Pijat Oksitosin oleh Suami terhadap Peningkatan Produksi Asi pada Ibu Nifas - Tabita Mariana Doko; Kun Aristiati; Suhoryo Hadisaputro (Jurnal Keperawatan Silampari, 2019)
The purpose of this study was to prove and verify the effect of oxytocin massage by the husband on increasing milk production in postpartum mothers. The method in this study uses a quasy experimental method with a non equivalent control group design approach. The results of the study, the administration of oxytocin massage by the husband affected the increased production of breast milk (ASI) with indicators of infant weight (p <0.05), frequency of breastfeeding (p <0.05), length of sleep of infants (p <0.05), frequency of discharges baby defecate (BAB) (p <0.05), frequency of urination of infants (BAK) (p <0.05), and resting mother's sleep (p <0.05). Conclusion, giving oxytocin massage by the husband can increase the production of Breast Milk (ASI) in postpartum mothers seen by the weight of the baby today, frequency of breastfeeding, length of sleep of infants, frequency of defecation of infants (BAB), frequency of defecation of infants (BAK) ), and resting mother's sleep. Keywords: Postpartum Mother, Oxytocin Massage by Husband, Breast Milk Production (ASI)